fNIRS Study of Brain Activation during Multiple Motor Control Conditions in Younger and Older Adults - Duoduo Yu; Conghui Wei; Zhen Yuan; Jun Luo (Journal of Integrative Neuroscience, 2024)
Background: Evidence suggests that aging contributes to decreased cerebral blood flow and brain oxyhemoglobin (HbO2) in the association cortices during rest. However, the influence of aging on functional brain activation is still controversial. The objective of this study was to investigate the age-related dependence of HbO2 across distinct motor control conditions in both primary and association cortices. Methods: Using functional near-infrared spectroscopy (fNIRS), this study assessed HbO2 level changes within the primary somatosensory cortex (PSC), primary motor cortex (PMC), supplementary motor cortex (SMC), prefrontal cortex (PFC) and dorsolateral prefrontal cortex (DLPFC) under various motor control conditions. Analysis examined changes in the concentration of HbO2 measured by fNIRS during rest, motor execution (ME), motor passivity (MP) and motor imagery (MI) with elbow flexion in 30 younger (21.5 ± 1.17 years old) and 30 older (60.9 ± 0.79 years old) adults. Results: During motor execution HbO2 was higher in younger adults than older adults in bilateral PMC, bilateral PFC, left PSC, left SMC and left DLPFC (p < 0.05). During motor passivity, HbO2 was higher in younger adults than older adults in bilateral PMC, left PSC and left SMC (p < 0.05). During motor imagery, HbO2 was higher in younger adults than older adults in bilateral PFC and bilateral DLPFC (p < 0.05). Conclusion: This study provided evidence that HbO2 levels are different in the primary and association cortices during different motor control conditions in young and old adults and that HbO2 levels in different brain regions under different motor control conditions can be influenced by age.